2023
DOI: 10.1029/2022jd038052
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional Wildfire Enhancements of PAN, C2H4, CH3OH, and HCOOH Over the Canadian High Arctic During August 2017

Abstract: Volatile organic compounds (VOCs) represent a large family of highly reactive and typically short-lived trace gases that reside in the Earth's atmosphere. VOCs have a broad range of primary and/or secondary sources, including anthropogenic emissions, biogenic production, and biomass burning. These reactive species can have wide-reaching direct and indirect effects on the air quality and climate of remote regions. In the Arctic, local sources of VOCs are limited, and their short atmospheric lifetimes generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 139 publications
(363 reference statements)
0
11
0
Order By: Relevance
“…12 and biased low injection heights of fire emissions. 59 The vertical profile of averaging kernels A z a (eq 1) describes the sensitivity of the satellite retrievals to concentrations as a function of altitude. Here, we see an order of magnitude increase in IASI PAN A z a from the PBL to the FT for the KORUS-AQ and ATom conditions (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 and biased low injection heights of fire emissions. 59 The vertical profile of averaging kernels A z a (eq 1) describes the sensitivity of the satellite retrievals to concentrations as a function of altitude. Here, we see an order of magnitude increase in IASI PAN A z a from the PBL to the FT for the KORUS-AQ and ATom conditions (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…Although the model overestimates PAN in the middle and upper FT in winter, it performs reasonably well in the PBL and lower FT where concentrations are high. The underestimate in summer could be due to an underestimate of PAN production in open-fire plumes and biased low injection heights of fire emissions …”
Section: Resultsmentioning
confidence: 99%
“…(2018, 2020), while detailed descriptions of the CH 3 OH, HCOOH, and PAN retrievals are provided in Wizenberg, Strong, Jones, Lutsch, et al. (2023) and references therein.…”
Section: Methodsmentioning
confidence: 99%
“…The GFASv1.2 inventory was selected over the default Global Fire Emissions Database, version 4.1 inventory (GFEDv4.1; Van Der Werf et al., 2017) as it was found that northern mid‐ and high‐latitude fires were better represented by GFAS when compared against satellite observations as discussed in Wizenberg, Strong, Jones, Lutsch, et al. (2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation